ANALISIS TINGKAT RISIKO KESEHATAN DAN KESELAMATAN KERJA (K3) DENGAN MENGGUNAKAN METODE HIRARC DI PT. XYZ - Muhammad Nur (Jurnal Teknik Industri Terintegrasi, 2021)
Occupational Health and Safety (K3) is an effort to prevent accidents and occupational diseases by recognizing the potential for accidents and occupational diseases. This study aims to determine the potential hazards at the Press station of PT. XYZ, knowing the risks of occupational safety and health and suggestions for prevention or control of occupational safety and health (K3). Data collection techniques using observation and interview methods. The analysis used is HIRARC (hazard identification risk assessment and risk control). Based on the results of this study, the potential hazards include hitting the head on an oil pipeline, slipping/falling, inhalation of dust, exposure to steam/odor, exposure to noise, and being blown away by hot steam. The results using the risk level matrix and the likelihood and concequence values are known to have 1 type of accident at a low risk level, 1 moderate risk level, 2 high risk levels and 2 extreme risk levels for work accidents. Risk control by using PPE in the form of safety helmets, shoes, masks, earplugs, wearpacks. Risk control that can be done is by using PPE in the form of safety helmets, shoes, masks, earplugs, wearpacks.